Synergistic Effects of Climate and Land-Cover Change on Long-Term Bird Population Trends of the Western USA: A Test of Modeled Predictions - Betts, Matthew G.; Gutiérrez Illán, Javier; Yang, Zhiqiang; Shirley, Susan M.; Thomas, Chris D. (Frontiers in Ecology and Evolution, 2019)
Climate and land-use change are predicted to lead to widespread changes in population dynamics, but quantitative predictions on the relative effects of these stressors have not yet been tested empirically. We analyzed historical abundance data of 110 terrestrial bird species sampled from 1983 to 2010 along 406 Breeding Bird Survey (BBS) across the northwestern USA. Using boosted-regression trees, we modeled bird abundance at the beginning of this interval as a function of (1) climate variables, (2) Landsat-derived landcover data, (3) the additive and interactive effects of climate and land-cover variables. We evaluated the capacity of each model set to predict observed 27-year bird population trends. On average, 45 species significantly declined over the period observed and only 8 increased (mean trend = -0.84%/year). Climate change alone significantly predicted observed abundance trends for 44/108 species (mean 0.37 ± 0.09 [SD]), land-cover changes alone predicted trends for 47/108 species (mean r = 0.36 ±0.09), and the synergistic effects predicted 59/108 species (mean r = 0.37 ±0.11). However, for 37 of these species, including information on land-cover change increased prediction success over climate data alone. Across stressors, species with trends that were predicted accurately were more likely to be in decline across the western USA. For instance, species with high correlations between predicted and observed abundances (> r = 0.6) were declining at rates that were on average >2%/ year. This indicates that abundance models have the capacity to predict the species most likely to be at risk from climate and land-use change, but for many species there were substantial discrepancies between modeled and observed trends. Nevertheless, our results highlight that climate change is already influencing bird populations of the western U.S. and that such effects often operate synergistically with land-cover change to affect population declines.